2014
DOI: 10.1186/1477-7525-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life is differently associated with leisure-time physical activity intensities according to gender: a cross-sectional approach

Abstract: BackgroundSeveral studies have demonstrated a positive association between physical activity (PA) and health-related quality of life (HRQL). However, studies have suggested that this association depends both on the PA intensity and the domain of HRQL evaluated. This study aimed to explore the association between physical, mental and overall HRQL with recommended levels of PA. PA levels were divided into moderate and vigorous intensity leisure-time PA and total leisure-time PA.MethodsThe study included 1001 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
6
23
0
3
Order By: Relevance
“…Furthermore, a positive association between PA and HRQoL in the elderly population has also been reported . Moreover, our findings are consistent with previous studies that reported positive relationships between leisure‐time PA and Physical Summary score and Mental Summary score in a healthy male and female adult population. However, the information is sparse between domain‐specific PA, including sitting time, and HRQoL in young adult men.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a positive association between PA and HRQoL in the elderly population has also been reported . Moreover, our findings are consistent with previous studies that reported positive relationships between leisure‐time PA and Physical Summary score and Mental Summary score in a healthy male and female adult population. However, the information is sparse between domain‐specific PA, including sitting time, and HRQoL in young adult men.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, health related quality of life (HRQoL) describes the general health and well-being of an individual with regard to symptoms and functioning and reflects how an individual values a particular state of health [3]. Hence, as health related quality of life can explain how people perceive their health and the specific physical, psychological, and social support needed in carrying out activities of daily life, it is important to investigate the associated factors [4]. …”
Section: Introductionmentioning
confidence: 99%
“…The QL goes beyond the absence of disease and overcoming the difficulties encountered in daily life. It can be influenced by multiple factors such as safety, transportation, education and housing [12,13,14]. The results showed that the QL of the mothers of children with microcephaly transcended the absence of disease, being influenced mainly by housing conditions and absence of transportation, among other factors.…”
Section: Resultsmentioning
confidence: 99%